Un mot peut en cacher un autre - Oven, Jacqueline (Vestnik za tuje jezike, 2015)
This article Un mot peut en cacher un autre (A Word Can Hide Another One) deals with the French function word de and its different uses, reflecting the multiple values of this word. Considering the multiplicity and complexity of its different uses, a study was done, based on a corpus, composed of FLE (French foreign language) students' examinations. We establish a list of right or wrong uses in order to analyse the data. In addition to the results of this study, the article also presents some more complex examples, which mostly combine the French preposition de and the article des.
Keywords: francoščina; French; tuji jeziki; francoska slovnična beseda de; predlogi; členi; slovenski študenti